2021
DOI: 10.1016/j.ajem.2021.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of post-COVID-19 deconfinement on psychiatric visits to the emergency department

Abstract: Objective During the deconfinement period after the coronavirus disease-2019 (COVID-19) pandemic, the number and characteristics of psychiatric visits changed in our emergency department (ED). We aimed to assess changes in the number of visits and characterize the profiles of these patients. Methods In this retrospective observational study, we examined the number of psychiatric ED visits and their proportion among the total number of ED visits. We also evaluated psychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…[17][18][19] The number of visits to the ED decreased worldwide during pandemic beginning, and our ED did not deviate from the rule. 20 This confirms our hypothesis that, in our ED, the number of visits decreased during the COVID-19 first wave and the non-COVID-19 patient visits were more urgent, based on the ESI triage tool.…”
Section: Discussionsupporting
confidence: 87%
“…[17][18][19] The number of visits to the ED decreased worldwide during pandemic beginning, and our ED did not deviate from the rule. 20 This confirms our hypothesis that, in our ED, the number of visits decreased during the COVID-19 first wave and the non-COVID-19 patient visits were more urgent, based on the ESI triage tool.…”
Section: Discussionsupporting
confidence: 87%
“…Other studies have also reported that a young age is one of the predictors of the appearance of the clinical signs of mental health disorders [ 26 , 28 , 31 ]. The sensitivity of this group is also emphasized by the observation that there was an increased psychiatric hospitalization rate for younger individuals during the pandemic [ 32 , 33 , 34 ]. In addition, younger people were also at an increased risk of committing suicide during this period [ 33 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shanghai was a typical city during the epidemic. First, Shanghai had a relatively small number of local COVID-19 cases and a high recovery rate in 2020, making it a role model for other major cities and provinces in China ( 21 ). The epidemic data were obtained from the official data released by the National Health Commission of China and the Shanghai Municipal Health Commission for the number of COVID-19 infected people from 0:00 on January 1, 2020, to 24:00 on December 31, 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, the research results are not consistent in different regions owing to the different stages of the epidemic and control policies. The number of PED visits could be decreased by COVID-19 stay-at-home orders ( 17 ) or fear of COVID-19 infection ( 18 , 19 ), varied by regions ( 20 ), and increased by the deconfinement period ( 21 ).…”
Section: Introductionmentioning
confidence: 99%